LOYALITAS NASABAH BANK SYARIAH: PERAN RELIGIUSITAS DAN KEPERCAYAAN - Intan Nurrachmi; Setiawan Setiawan (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2020)
AbstractIslamic bank products must attract the interest and loyalty of their customers, by providing a sense of security and instilling customer confidence in the bank. Most Sharia bank customers are Muslims. However, if a Sharia bank is limited to only Muslim customers, it will hamper the development of the bank, then Sharia banks must be able to attract customers, both Muslims and non-Muslims. This study examines the loyalty of Islamic bank customers from the role of religiosity and customer trust. This research was conducted to Sharia bank customers in the city of Bandung with a random sampling method, data were collected through questionnaires and proof of hypothesis using Structural Equation Modeling - Partial Least Square (SEM - PLS) analysis. The test results state that: religiosity has a significant effect on trust; religiosity has a significant effect on loyalty; trust has a significant effect on loyalty; and religiosity has a significant effect on loyalty through trust.